Activization of Ethnology Studies in the System of the Future Philologists Preparation: Historical Aspect - Olesya Bartashuk (Pedagogical Discourse, 2013)
On the basis of the analysis of different approaches to classification of the source base of ethnology as historic-humanitarian discipline, optimum sources of its study through the prism of preparation of Ukrainian philologists with the accent to the regional aspect are determined. In particular, one of the most effective sources reflects not only general principles of scientific source study, bit also reveales the history of interrelations of ethnology, bélles-léttres, historic science, philological disciplines, the works from the school course of Ukrainian bélles-léttres are determined. Taking into account regional aspect of the sourse study of ethnological science, much attention is paid to the periodics, materials of scientific conferences, and professional collections.